Kültürel Alanda Reklam Ve İletişim Stratejisi - Kılanç, Ruken Özgül (The Turkish Online Journal of Design, Art and Communication, 2012)
The media, which offers limitless possibilities, represents the interlocking cultural environment of our day; television series, advertisements, competitions, virtual platforms present at the same time all around the world and the loneliness created by these environments underline the value of digital mediums. Television has a huge role as a digital advertising mean; as a medium that calls out to the five senses, it has an effective role as a medium. Furthermore, because television can reach out to more than one person in the same environment at the same time, it also serves as a cultural forger. Individuals living away from their homelands use television in order to keep their ties with their home countries. There are specific advertisements targeted at these migratory cultures; these advertisements keep communities together as they are equipped with visual indicators that uphold traditional customs and values. Thus institutions uphold their missions, visions and ideolojies through the advertisement or the name of the brand advertised. In our study, we will be looking at the visual reflection of brand advertisements directed at people living away from their home countries and how institutions impose their ideolojies visually. UsingMarshall McLuhan’s “the medium is the message” statement, cultural indicators used to convey the ideological messages will be determined. In this study, a survey was conducted with Turkish immigrants living in Holland; through this survey, their cultural ideology was determined. In the advertisement chosen, the links between the ideological approach of the brand name and the ideological approach of the immigrants was evaluated and analyzed.
Keywords: Digital Media; Migration; Cultural Sphere; Visual İndicator; Brand; Dijital Medya; Göç; Kültürel Küre; Görsel Göstergesi; Marka